Ergonomics in the operating room and surgical training: a survey on the Italian scenario - Restaino, Stefano; D’Indinosante, Marco; Perelli, Federica; Arcieri, Martina; Cherchi, Vittorio; Petrillo, Marco; Cavaliere, Anna Franca; Cianci, Stefano; Pellecchia, Giulia; Meniconi, Roberto Luca; Coppola, Alessandro; Chiantera, Vito; et al. (Frontiers in Public Health, 2024)
INTRODUCTION Surgical-related injuries are frequent, in fact the reported percentage of musculoskeletal disorders in surgeons is between 47% and 87 %. This survey aims to assess the Italian overview both highlighting how prevalent surgical-related injury is in our surgeons and whether there is an operating room ergonomics education program in Italian surgical specialty schools. METHODS An anonymous questionnaire was designed through SurveyMonkey© web application. This survey was composed of 3 different sections concerning the general characteristics of the participants, their surgical background and any training performed, and any injuries or ailments related to the surgical activity. The survey was carried out in the period 1th of December 2022 and the 6th of February 2023 RESULTS At the close of our survey, 300 responses were collected. Among the participants, the two most represented specialties were Gynecology and Obstetrics (42.3%) and General Surgery (39.7%). and surgeons were mainly employed in the Northern regions of Italy (54.8%). Analyzing the participants' background (see Table 4), 61.7% of the respondents had laparoscopic training during their training and only 53.1% had a pelvic trainer during their residency. In accordance with 98.7% of the respondents, during surgery we have the feeling of being in an uncomfortable position that causes discomfort or muscle pain, and regarding the frequency of these discomforts, the majority of our study population experiences these problems monthly (46.2%), while in 29.6% it is experienced weekly, 12.1% annually and finally 12.1% daily. The surgical approach that is most correlated with these disorders is laparoscopy (62.7%) while the one that causes the least discomfort is robotic surgery (1.4%). These discomforts cause 43.9% of our population to take a break or do short exercises to reduce pain during surgery, and the body areas most affected are the back (61.6%), neck (40.6%) and shoulders (37.8%). CONCLUSION Despite this, our survey allows us to highlight some now-known gaps present in the surgical training program of our schools and the lack of protection towards our surgeons during their long career.